Quarantine 2 [videorecording (DVD)] : terminal - Pogue, John; Pogue, John; Masöhn, Mercedes, 1982-; Cooke, Josh, 1979-; Serricchio, Ignacio, 1982- (Sony Pictures Home Entertainment, 2011)
Earlier tonight, a bizarre disease was unleashed in a run-down Los Angeles tenement--and no one got out alive. Yet something escaped. Now, aboard Flight 318, the first symptoms begin to show. As the infection begins to take root, innocent passengers suddenly transform into terrifying, bloodthirsty killers. Forced to land at an isolated terminal, and surrounded by armed government agents, the crew and passengers grow increasingly desperate. The only question now is how far they will go to survive.